Guide to the availability of theses - Allen, G. G.; Deubert, K.; Borchardt, D. H.; International Federation of Library Associations and Institutions (München : New York : K.G. Saur, 1984)
The compilers of this volume have relied extensively on the work of D.H. Borchardt. His observations on the relevance of theses to both the UBC and UAP programmes of IFLA are endorsed, and his comments on national or institutional practices and on terminology apply equally to the present compilation.
Supplement to: Guide to the availability of theses / D. H. Borchardt, 1981.
Includes indexes.
rpm 14/02/2019
Loans
Keywords: Dissertations, Academic